2020
DOI: 10.1016/j.vaccine.2020.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Fatal outcomes following immunization errors as reported to the EudraVigilance: A case series

Abstract: Background: Serious adverse reactions after immunization are rare but do occur. In very rare instances, cases with fatal outcome have been reported. These reports can have a huge impact and even more so when due to an immunization error. The aim of this study is to systematically review immunization errors with fatal outcomes in EudraVigilance. Methods: This was a case-series analysis of Individual Case Safety Reports (ICSRs) reporting immunization errors and a fatal outcome. To determine the level of certaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…This study highlights the importance of measures to improve visually distinguishing features of vaccines and medicines. 16 In the European Union, clear guidelines are in place to limit similarity in packaging. 17 The WHO has released recommendations to limit confusion between vaccines and medicines by, for example, separate storage places for these products.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the importance of measures to improve visually distinguishing features of vaccines and medicines. 16 In the European Union, clear guidelines are in place to limit similarity in packaging. 17 The WHO has released recommendations to limit confusion between vaccines and medicines by, for example, separate storage places for these products.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries neither have well-defined surveillance and reporting systems nor trained professionals to detect AEFIs, assess causality, manage AEFIs, and eliminate confounders [ 36 , 37 ]. Hoeve et al identified 154 potentially biased individual case reports on AEFIs that cannot be directly attributed to vaccines but could have occurred from non-compliance to recommended immunization schedules [ 38 ]. Healthcare professionals specialized in this discipline have a significant role in separating and resolving confounders from genuine AEFIs.…”
Section: Discussionmentioning
confidence: 99%
“…Desde que os erros de medicação foram identificados como os mais comuns na prestação de cuidados à saúde (KOHN; CORRIGAN; DONALDSON, 2000), outros estudos específicos para EI decorrentes de vacinação têm contribuído para sua compreensão (ARSHI et al, 2003;AZAR et al, 2021;BARBOZA et al, 2020;BISETTO, 2017;BRASIL, 2018a;BRITO, 2014;CABELLO;ORTIZ, 2020;CAPPONI;PAZ, 2020;CONDON;HAYNEY, 2016;HAMPTON, 2020;HIBBS et al, 2015;HOEVE et al, 2018;HOEVE et al, 2020;LANG et al, 2014;LEE et al, 2021;LIU et al, 2022;MORO et al, 2019;PACHECO et al, 2018;REED;TARINI;ANDREA, 2019;REES et al, 2015;PASCHOALOTTO;BRUNIERA, 2012;SILVA, T. et al, 2021;WALLIS;DOVEY, 2011).…”
Section: Imunizaçãounclassified